2022
DOI: 10.3389/fonc.2021.785297
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Polyphosphate 4-Phosphatase Type II Is a Tumor Suppressor in Multiple Myeloma

Abstract: Inositol polyphosphate-4-phosphatase type II (INPP4B) has been identified as a tumor suppressor, while little is known about its expression and function in multiple myeloma (MM). In this study, we evaluated the expression of INPP4B in 28 cases of newly diagnosed MM patients and 42 cases of extramedullary plasmacytoma (EMP) patients compared with normal plasma cells and found that low INPP4B expression was correlated with poor outcomes in MM patients. Moreover, expression of INPP4B in seven MM cell lines was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…In the study presented, INPP4B overexpression reduced proliferation, viability, and growth of etoposide-resistant RB cell lines and concomitantly increased caspase-3/7 mediated apoptosis levels, supporting INPP4B`s role as a tumor suppressor in RB cells. Consistent with our data, it has been demonstrated that INPP4B overexpression inhibits cervical and human hepatocellular carcinoma (HCC) as well as multiple myeloma and acute myeloid leukemia, cell proliferation, and induces caspase-3-mediated apoptosis in HCC cell lines [ 10 , 21 , 31 ]. Similarly, INPP4B knockdown increased the proliferation of human basal-like breast cancer cells [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the study presented, INPP4B overexpression reduced proliferation, viability, and growth of etoposide-resistant RB cell lines and concomitantly increased caspase-3/7 mediated apoptosis levels, supporting INPP4B`s role as a tumor suppressor in RB cells. Consistent with our data, it has been demonstrated that INPP4B overexpression inhibits cervical and human hepatocellular carcinoma (HCC) as well as multiple myeloma and acute myeloid leukemia, cell proliferation, and induces caspase-3-mediated apoptosis in HCC cell lines [ 10 , 21 , 31 ]. Similarly, INPP4B knockdown increased the proliferation of human basal-like breast cancer cells [ 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…INPP4B levels are significantly reduced in human hepatocellular, gastric, and gallbladder carcinoma [ 10 , 28 , 29 ]. In a most recent study, decreased INPP4B expression levels were reported for multiple myeloma cell lines as well as bone marrow plasma of multiple myeloma patients, and lower INPP4B levels correlated with a poor outcome [ 31 ]. Fittingly, in the study presented, we demonstrated that compared to the healthy human retina INPP4B mRNA expression levels are significantly decreased in RB cell lines, indicating a tumor-suppressing role of INPP4B in retinoblastoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations